2016
DOI: 10.1002/pbc.25976
|View full text |Cite
|
Sign up to set email alerts
|

Evans Syndrome at Childhood‐Onset Systemic Lupus Erythematosus Diagnosis: A Large Multicenter Study

Abstract: Our large multicenter study identified ES as a rare and severe initial manifestation of active cSLE with good outcome. Diagnosis is challenging due to the lack of typical signs and symptoms of lupus and the requirement to exclude infection and primary immunodeficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 47 publications
0
16
0
2
Order By: Relevance
“…The incidence of ES in children is unknown due to a lack of published studies, with the few available consisting of case reports or retrospective cohorts. 6 , 12 , 59 , 74 76 From the largest cohorts of autoimmune cytopenias, it can be concluded that ES is more frequent during childhood; in a study, 11 (4.1%) of 179 children had ES 6 vs 6 (0.78%) of 766 adults. 77 It is important to note that autoimmune cytopenias in children are frequently associated with primary immunodeficiencies and in this group, they should always be ruled out.…”
Section: Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of ES in children is unknown due to a lack of published studies, with the few available consisting of case reports or retrospective cohorts. 6 , 12 , 59 , 74 76 From the largest cohorts of autoimmune cytopenias, it can be concluded that ES is more frequent during childhood; in a study, 11 (4.1%) of 179 children had ES 6 vs 6 (0.78%) of 766 adults. 77 It is important to note that autoimmune cytopenias in children are frequently associated with primary immunodeficiencies and in this group, they should always be ruled out.…”
Section: Classificationmentioning
confidence: 99%
“…Several studies have demonstrated the relationship between SLE and ES; 9 , 10 , 58 prevalence of secondary ES in SLE has been reported in 1.7%–2.7% of cases. 24 , 59 Hemorrhagic manifestations are frequently observed in this group, including petechiae, ecchymosis, epistaxis, gingivorraghia, gastrointestinal bleeding and hematuria. 5 , 59 Spontaneous splenic rupture as an initial manifestation of ES has been documented, 60 confirming the heterogeneous course of the disease.…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…LA includes 33 countries and dependencies, a large population, two main languages (Spanish and Portuguese), with distinct socio-economic and political status. Two groups have reported data focused on epidemiology, clinical and laboratorial features of cSLE patients in LA: BRAC-SLE (Brazilian Childhood-onset SLE Registry Group) [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and GLADEL (Grupo Latino Americano De Estudio del Lupus) [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…2,16,17 The longest time interval to diagnosis observed in the present study occurred in a patient with hematological complications, also reported in other studies. 18…”
Section: Discussionmentioning
confidence: 99%